(untitled) (Al-Academy, 2026)
The significant potential of mind maps in analyzing contemporary visual texts remains an area requiring deeper exploration. This study investigates the communicative discourse of mind maps and their manifestations in interpreting contemporary visual art. It aimed to identify the nature of this discourse and how it functions in reading artistic texts. The theoretical framework covered concepts of discourse, the development of mind maps, and reader-response theories by Jauss and Iser. A descriptive-analytical method was adopted, analyzing 5 artworks selected from a pool of 25. The findings highlighted interactive engagement between artwork and viewer, consistent with Iser’s “textual gaps” and Jauss’s “aesthetic distance.” The study concluded that reception is not merely cognitive, but a cultural practice reshaping the artwork through dynamic, context-sensitive interpretation. Recommendations and suggestions concluded the study